Assessing the Quality of Compost Tea Made from Swamp-Growing Lotus Plants - Tri Putri Nur; Susilawati; Priatna, Satria Jaya; Marsi; Gofar, Nuni (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2023)
Lotus is a wild plant in wetlands that have not been widely used but has great potential to be developed as compost tea. Therefore, this research aims to evaluate the content of compost tea made from wild lotus found in wetlands, which has not been sufficiently used but has great potential to be developed as compost tea. It was conducted by testing several methods and compositions of compost immersion, namely A1, A2, A3, and A4 at Aeration 1:5, Aeration 1:10, Non-aeration 1:5, and Non-aeration 1:10, respectively. The results show that the pH value increased until day 8 of immersion and then decreased on days 9 and 10, with a range of 8.0-8.44, in the recommended range. Furthermore, the total dissolved solids in the 1:5 water ratio were lower than the 1:10 of compost and water. The content of nutrients (C-organic, N-total, and P-available), bacteria population, actinomycetes, fungi, and humic acid concentration were higher in aeration treatments for both 1:5 and 1:10 compost and water ratios. In addition, humic acid functional groups in compost tea for all treatments were detected, including OH-phenolic, C=C, C=C, COOH, CH3, secondary amides, and tertiary amides with different wavelengths. Based on these results, it can be concluded that aeration treatment provides better results for the observed variables than non-aeration. Keywords: Compost tea, humid acid, liquid organic fertilizer, lotus, nutrient content.